Probiotics and its Impact on Antibiotic-associated Diarrhea (AAD) and Clostridum difficile Infections (CDI) in Adult and Pediatric Patients: A Review - Chakraverty, Raja; Sasmal, Sudeshna (Journal of Pharmacy Practice and Community Medicine)
A common adverse effect of antibiotic use is diarrhea. Probiotics are living micro-organisms, which may prevent antibiotic-associated diarrhea (AAD) by the normalization of an unbalanced gastrointestinal flora. The objective of this review was to assess the benefits and harms of probiotics used for the prevention of AAD in patients based on literature findings. Thus review of the literature using bibliographic databases and abstracting systems such as PubMed (1978- 2020) and Cochrane was conducted to find the effects of probiotics and compare AAD and CDI in both pediatric and adult populations and determine significant differences and similarities that might impact clinical decisions. In general, pediatric AAD and CDI have a more rapid onset of symptoms, a shorter duration of disease and fewer CDI complications (required surgeries and extended hospitalizations) than in adults. Literature studied revealed the finding that suggests that probiotic use in both adult and populations may be beneficial in the prevention of AAD among patients. Furthermore, the use of probiotics appears to be safe. The narrative review adds value to the current knowledge owing to the fact that adult and pediatric differences of AAD and CDi have not been studied in many review focusing on current evidence before ours. The differences in treatment modality across age groups should be taken into account when rating severity of disease and prescribing antibiotics. However, any differences should be taken into account when rating severity of disease and prescribing.
Keywords: Antibiotics; Antibiotic-associated diarrhea; Clostridum difficile infections; probiotics; Lactobacillus; Bifidobacterium; Saccharomyces